Michael Culture Association - (:unkn) unknown (My University, 2026)
Michael Culture Association (Aisbl - Belgium) is an European trans-domain devoted to European digital cultural heritage valorisation. It gathers a strong network of more than 100 public and private organizations from all over Europe. Key actor in the promotion and valorization of the digital cultural content, Michael Culture develops tools and services for cultural institutions and the general public. Linked to other major European cultural heritage networks and projects such as Europeana, Europe's Digital Library, Michael Culture Association supports European and national cultural policies. It also aims at enhancing the network of European professionals working on digital cultural heritage and advocating for DCH.